2020
DOI: 10.1101/2020.07.01.183327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome analysis of alternative splicing-coupled nonsense-mediated mRNA decay in human cells reveals broad regulatory potential

Abstract: AbstractTo explore the regulatory potential of nonsense-mediated mRNA decay (NMD) coupled with alternative splicing, we globally surveyed the transcripts targeted by this pathway via RNA-Seq analysis of HeLa cells in which NMD had been inhibited. We identified putative NMD-targeted transcripts as those with a termination codon more than 50 nucleotides upstream of an exon-exon junction (premature termination as defined by the ‘50nt rule’) and that significantly increased in abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 129 publications
(166 reference statements)
3
4
0
Order By: Relevance
“…The latter association is consistent with the model that long 3′UTRs can function as NMD-activating features. Together, these associations matched those observed for other NMD loss-of-function models, e.g., in HeLa cells subjected to UPF1 knockdown ( 24 ). Together, we concluded that our genetic model based on the mutant Smg6 allele was suitable to analyze endogenous targets and functions of the NMD pathway.…”
Section: Resultssupporting
confidence: 83%
“…The latter association is consistent with the model that long 3′UTRs can function as NMD-activating features. Together, these associations matched those observed for other NMD loss-of-function models, e.g., in HeLa cells subjected to UPF1 knockdown ( 24 ). Together, we concluded that our genetic model based on the mutant Smg6 allele was suitable to analyze endogenous targets and functions of the NMD pathway.…”
Section: Resultssupporting
confidence: 83%
“…Altogether these associations match those observed for other NMD loss-of-function models, e.g. in Hela cells subjected to Upf1 knockdown 22 . Taken together, we concluded that our genetic model based on mutant Smg6 was suitable to analyze endogenous targets and functions of the NMD pathway.…”
Section: A Novel Conditional Nmd Loss-of-function Allele Based On Smg...supporting
confidence: 86%
“…We calculated the iNMDeff for the different NMD gene sets from each study separately (see Methods): “Karousis” 13 , “Colombo” 5 , “Tani” 6 , and “Courtney” 51 , and we further tagged the transcripts as “nonsense_mediated_decay” from the Ensembl gene annotation as an additional “Ensembl’’ set. Additionally, genes found in at least 2 independent studies constituted a “NMD Consensus” gene set, and the union of genes across all studies was the “NMD All” gene set.…”
Section: Resultsmentioning
confidence: 99%
“…We started with an initial set of genes that had been experimentally identified as endogenous NMD target genes from various studies that perturbed NMD activity in human cell lines 5,6,13,14,51 (see Methods). For each gene, we categorized its transcripts into NMD targets and controls based on computationally predicted NMD-triggering features (see Methods and Supp.…”
Section: Endogenous Target Gene (Etg) Methodmentioning
confidence: 99%